Design, construction and installation of a wind tunnel for testing small wind turbines - Gonzáles Chávez, Salome (2011)
This article is referred to the design, construction and functioning of a Wind Tunnel opened, installed in the Energy Laboratory of the Mechanical Engineering Faculty, Universidad Nacional de Ingeniería, FIM-UNI, it used to research and experimental tests of wind generator models, testing circuit performing evaluations to improve the system of orientation, safety of turbine and permanent magnet generator optimization. This tunnel was installed in July 2008, by specific action of agreement between the Mechanical Engineering Faculty, FIM-UNI and SOLUCIONES PRÁCTICAS-ITDG, as part of the joint research in the development and optimization of small wind turbines for the electrification of isolated Peruvian rural populations. Tunnel basically consists of three parts: collector, stagnation chamber and diffuser; calculations were made using compressible flow equations. As a result of appropriate design, obtained tunnel reaches a maximum speed of 15 m/s with the model test.